Cochrane Database of Systematic Reviews 2000
DOI: 10.1002/14651858.cd002137
|View full text |Cite
|
Sign up to set email alerts
|

Reduced or modified dietary fat for preventing cardiovascular disease

Abstract: BACKGROUND: Reduction and modification of dietary fats have differing effects on cardiovascular risk factors (such as serum cholesterol), but their effects on important health outcomes are less clear. OBJECTIVE: To assess the effect of reduction and/or modification of dietary fats on mortality, cardiovascular mortality, cardiovascular morbidity and individual outcomes including myocardial infarction, stroke and cancer diagnoses in randomised clinical trials of at least 6 months duration. METHODS:Search methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 324 publications
6
81
0
4
Order By: Relevance
“…This review is more specific in addressing the role of polyunsaturated fats than the previous systematic review, which addressed cardiovascular health effects of reduced saturated fats 3. The earlier review found that reductions in cardiovascular events only where saturated fats were replaced by unsaturated fats in studies of at least 2 years – findings consistent with those of Mozaffarian and colleagues.…”
Section: Findings Consistent With Previous Researchsupporting
confidence: 60%
“…This review is more specific in addressing the role of polyunsaturated fats than the previous systematic review, which addressed cardiovascular health effects of reduced saturated fats 3. The earlier review found that reductions in cardiovascular events only where saturated fats were replaced by unsaturated fats in studies of at least 2 years – findings consistent with those of Mozaffarian and colleagues.…”
Section: Findings Consistent With Previous Researchsupporting
confidence: 60%
“…A previous large scale search for dietary trials and cardiovascular disease covered the Cochrane library, Medline, Embase, CAB abstracts, CVRCT registry, and SIGLE to May 1998 plus bibliographies of collected papers and reviews 9. We carried out a further search, seeking trials on sodium restriction and blood pressure in Medline, Embase, and the Cochrane library (to July 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Much of the methodology has been reported previously 9. Briefly, we developed a search strategy to search for nutrition based randomised controlled trials on the Cochrane Library, Medline, Embase, CAB abstracts, CVRCT registry (inception of database to mid-1998), and SIGLE (January 1999).…”
Section: Methodsmentioning
confidence: 99%